The Role of Volunteered Geographic Information towards 3D Property Cadastral Systems (2): A Purpose Driven Web Application - Almeida, J.-P. de (2016)
VGI has not proved to be readily suitable to replace well-established accurate methods and technologies such as those of full standard cadastral surveys. Even so, VGI potentialities as relevant source of geospatial data have been widely acknowledged. As such, some authors have defended that VGI may in fact play an important role such as at a local cadastral jurisdiction level towards local spatial data infrastructures. As far as property cadastre is concerned, the full extent 3D complexity inside a property is in many instances only known to their occupants, thus making crowd sourcing perhaps the only economically feasible approach for its capture. While the crowd cannot be expected to conduct a full cadastral survey, it may be possible to ask them to indicate at least the location of complex 3D situations and thus to facilitate local authorities’ understanding of the extent of some cadastral issues. As such, it was argued in our previous work that geoinformation from the crowd might in fact be taken into account as an interim step before a full surveyed 3D cadastre is eventually achieved. As such, possible room for VGI in the context of 3D cadastre was discussed, and a hierarchical framework of levels of data acquisition to be used at local cadastral jurisdiction level was proposed. Such framework is revisited in this paper.Given context above, this paper focuses primarily on two aspects. Firstly, to review technical requirements of the official cadastral process in Portugal in order to identify which sorts of cadastral data are likely to be acquirable/not acquirable through VGI. Secondly, to design and to implement the prototype of a web-based application (IGV3Dcad) envisaged for general public usage to flag different land and property ownership situations. Having information about the extent of the 2D/3D issue is also fundamental to making a decision as to whether a 3D cadastral approach is actually needed and hence to further invest resources in even more expensive 3D survey.